1996
DOI: 10.1111/j.1699-0463.1996.tb04950.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of IL‐2‐activated natural killer cells in vitro: influence of extracellular matrix proteins

Abstract: An experimental set‐up for estimating a) cellular migration under agarose and b) response to chemoattractant gradients built up in the agarose was used in order to explore the behavior of adherent interleukin‐2 (IL‐2)‐activated natural killer (A‐NK) cells on cell culture plastic and after coating with extracellular matrix (ECM) constituents. A‐NK cells were deposited in wells in the agarose and directed migration, chemotaxis, towards aggregates and suspensions of B16F10 melanoma cells, suspensions of YAC‐1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…ents of basal membranes (Martin and Timpl, 1987). In several in vitro assays, matrix proteins have been shown to provide a substrate for migration of NK cells (Ratner et al, 1992;Unger et al, 1996;Johansson and Nannmark, 1996;Somersalo and Saksela, 1991) and may also enhance lytic activity of IL-2 cultured lymphocytes (Li et al, 1997). In the CC531 tumor model, matrix proteins seem to have an ambiguous role regarding the infiltration of tumor nodules by A-NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…ents of basal membranes (Martin and Timpl, 1987). In several in vitro assays, matrix proteins have been shown to provide a substrate for migration of NK cells (Ratner et al, 1992;Unger et al, 1996;Johansson and Nannmark, 1996;Somersalo and Saksela, 1991) and may also enhance lytic activity of IL-2 cultured lymphocytes (Li et al, 1997). In the CC531 tumor model, matrix proteins seem to have an ambiguous role regarding the infiltration of tumor nodules by A-NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that gp-340 stimulates chemokinesis of alveolar macrophages drives speculation into possible functions for gp-340 in the lung that are diverse yet intriguing. Known protein stimulators of chemokinesis can be grouped into three main categories: growth factors, such as plateletderived growth factor-AB, vascular endothelial growth factor, fibroblast growth factors, and epidermal growth factors (29)(30)(31); extracellular matrix (ECM) and adhesion molecules, such as fibronectin, laminin, thrombin, and collagen (32)(33)(34); and immune and inflammatory regulators (such as C1q; interleukins 2, 4, 5, and 8; and platelet-activating factor) (35)(36)(37)(38)(39)(40).…”
Section: Gp-340 As a Secreted Protein In Lung Lavage: Potential Functmentioning
confidence: 99%
“…ECM-stimulated chemotaxis has been implicated in the recruitment of neutrophils to inflammatory sites (32) and the development of an organized vascular system in the mouse embryo (34). Similarly, the induction of random migration by immune activators is thought to be a first step in cell locomotion (37), an important step in the initiation of the extravasation of neutrophils and other inflammatory cells (35), the homing of lymphocytes and natural killer cells (38,40), and the initiation of eosinophil-and mast cell-based inflammation (37,39). These roles for chemokinetic proteins lead to the possibility that gp-340 is involved in such activities as the regulation of lung inflammation, the recruitment of monocytes into the lung and/or the regulation of their differentiation, the recruitment of macrophages and/ or fibroblasts to sites of lung injury, the embryonic development of the highly vascularized lung, or the adhesion of macrophages to the epithelium.…”
Section: Gp-340 As a Secreted Protein In Lung Lavage: Potential Functmentioning
confidence: 99%
“…Rather, they must migrate across the stroma, possibly using the stromal matrix fibers as a substratum for migration. Both in vitro and in vivo studies have demonstrated that this may indeed be the case [12,18,31,33].…”
Section: Discussionmentioning
confidence: 94%